The Stories They Carried: Reflections of Vietnamese-Canadians 40 Years after That War - Koh, Priscilla (Refuge: Canada’s Journal on Refugees, 2016)
This article explores the narratives of former refugees from Vietnam who resettled in Canada. Each of these stories highlights the profound dilemmas, motivations, and experiences of Vietnamese refugees. Collectively, they demonstrate the remarkable resilience of this community, and their determination to survive and remake themselves in Canada. The discussion illuminates the diversity and complexity of my respondents’ senses of belonging, homes, and homelands, and how such notions and ties are continually evolving. The research aims to contribute to the postwar/refugee discourse, and to move the field beyond the parameter of the war and exodus from Vietnam, in order to study Vietnamese in all their complexities—in a new locale.